Pengaruh Pemakaian Demulsifier A Dan B Terhadap Crude Oil Lapangan KB Dengan Metode Bottle Test: Demulsifier Using Bottle Test Method - Erik Indra Putra (BBPMGB LEMIGAS, 2025)
The stability of water-in-crude oil emulsions poses a significant challenge in oil production and refining processes, particularly in KB Field, which exhibits highly stable emulsion characteristics. This study aims to evaluate the effectiveness of two types of demulsifiers—Demulsifier A and Demulsifier B—in separating water from crude oil emulsions using the bottle test method. Tests were conducted at varying concentrations (0, 200, 300, and 400 ppm), with analysis of water drop and Sediment and Water (S&W) values across two sample zones: top cut and mix cut. Results indicate that Demulsifier A demonstrates superior performance, reducing S&W values to as low as 0.2% at 400 ppm, while Demulsifier B shows stagnation at higher concentrations. These findings contribute to the selection of more efficient chemical agents for demulsification processes and support the development of more sustainable and cost-effective production strategies. The study also highlights the importance of quantitative approaches in demulsifier evaluation, which remain limited in local literature.